Efektivitas Model Pembelajaran Guided Inquiry Berbasis Geoliteracy (GIGL) Terhadap Kemampuan Berpikir Spasial Pada Pelajaran Geografi - Dian Puspita Anggreni; Sumarmi Sumarmi (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2022)
The spatial thinking ability is necessary in studying geography. Geographical material that discusses phenomena on earth requires the spatial thinking ability for applying a geographic approach. The purpose of the following study was to determine the effectiveness of the learning guided inquiry based on geoliteracy (GIGL) of spatial thinking ability. The research subjects used experimental and control classes which were selected by paying attention to the similarity of characteristics. The research was carried out in class X IPS at SMA Negeri 1 Pracimantoro. The research design used a non-equivalent control group design. Spatial thinking ability data analysis using T-test analysis with a significance of 0.05. The results of data analysis using the T-test show that there are differences in the ability to think spatially between students using the learning guided inquiry based on geoliteracy and students using the conventional learning model.